Blood Profile of Lactating Cows Supplemented with Organic Chromium and Ganoderma lucidum - Agustin, F.; Toharmat, T.; Evvyernie, D.; Taniwiryono, D.; Tarigan, S. (Pakistan Journal of Nutrition, 2012)
The aim of this experiment was to determine blood profile (hemoglobin, hematocrit, red blood cells, white blood cells), differential leucocytes count (neutrophils, lymphocytes, monocytes, eosinophils) and chromium in blood of lactating cows supplemented with organic chromium (Cr) and Ganoderma lucidum in ration. Fifteen lactating cows grouped and allocated in the five treatments in randomize block design, were fed a basal diet composed of 60% grass and 40% concentrate. Supplementation on basal diet as treatment were: A = basal diet (control), B = 3 ppm inorganic Cr in CrCl3.6H2O, C= 3 ppm organic Cr (fermentation product with Ganoderma lucidum), D = Ganoderma lucidum (5 g 50 kg-1 live weight) and E = Organic Cr+Ganoderma lucidum. Blood profile, differentiation of leucocytes and chromium in blood were investigated. The result showed that there were no significant differences on blood profile (p>0.05). Total leucocytes count was 7120±1.44 cell/μl in treatment E to 9270±2.32 cell/μl in control. Also, organic Cr and Ganoderma lucidum supplementation had no significant effect on differential leucocytes counts and chromium in blood (p>0.05). It can be concluded that blood profile, differential leucocytes count and chromium in blood of lactating cows have not been affected by supplementing organic chromium and Ganoderma lucidum in ration.